Answer:
[tex]f(x)=5(x-2)^{2}+6[/tex]
Step-by-step explanation:
we have
[tex]f(x)=5x^{2} -20x+26[/tex]
This is the equation of a vertical parabola open upward
The vertex is a minimum
The equation of a vertical parabola in vertex form is equal to
[tex]f(x)=a(x-h)^2+k[/tex]
where
(h,k) is the vertex
Convert the given function to vertex form
Factor the leading coefficient
[tex]f(x)=5(x^{2} -4x)+26[/tex]
Complete the square
[tex]f(x)=5(x^{2} -4x+4)+26-20[/tex]
[tex]f(x)=5(x^{2} -4x+4)+6[/tex]
Rewrite as perfect squares
[tex]f(x)=5(x-2)^{2}+6[/tex] ------> equation in vertex form
The vertex is the point (2,6)